Development of Novel CD47-Specific ADCs Possessing High Potency Against Non-Small Cell Lung Cancer in vitro and in vivo - Chiang, Zu-Chian; Fang, Shubin; Shen, Yang-kun; Cui, Dongya; Weng, Huanjiao; Wang, Dawei; Zhao, Yuxiang; Lin, Jizhen; Chen, Qi (Frontiers in Oncology, 2022)
Targeted therapies hold promise for efficiently and accurately delivering cytotoxic drugs directly to tumor tissue to exert anticancer effects. CD47 is a membrane protein expressed in a variety of malignant tumors and hematopoietic cells, which plays a key role in immune escape and tumor progression. Although CD47 immunocheckpoint therapy has been developed in recent years, many patients cannot benefit from it because of its low efficiency. To strengthen and extend the therapeutic efficacy of anti-CD47 monoclonal antibody (mAb), we used the newly developed 7DC2 and 7DC4 mAbs as the targeting payload adaptor and VCMMAE as the toxin payload to construct novel CD47-specific immunotoxin (7DC-VCMMAE) by engineering cysteine residues. These CD47-specific ADCs have the better cell penetration, excellent DAR, similar payload distribution and good antigen-binding affinity. In vitro, 7DC-VCMMAE treatment induced death of non-small cell lung cancer (NSCLC) cell lines 95D and SPC-A1, but not A549 that express low levels of CD47 on the cell membrane. This finding suggests that 7DC-VCMMAE may possess greater therapeutic effect on NSCLC tumors expressing a high level of CD47 antigen; however, 7DC-VCMMAE treatment also promoted phagocytosis of A549 cells by macrophages. In vivo, 7DC-VCMMAE treatment had remarkable antitumor effects in a NSCLC cell line-derived xenograft (CDX) mouse model based on nonobese diabetic/severe combined immunodeficient (NOD/SCID). In summary, this study combined VCMMAE with anti-CD47 mAbs, emphasizing a novel and promising immunotherapy method for direct killing of NSCLC, which provides a valuable new way to meet the needs of the cancer therapy field.